A study on the wage disparity between employees with and without disabilities: Evidence from South Korea - Mi-Ok Kim; Sung-Joon Huh; Hyung-Rok Jung (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this study is to identify whether wage discrimination against people with disabilities exists in the Korean labor market and, if so, to understand the cause and level of wage discrimination. Design/methodology/approach: We first conducted Heckman's two-stage model to control human resource and market characteristics, using the Korean Labor Panel and the Employment Panel for Persons with Disabilities. Next, we analyzed the existence and cause of wage discrimination through reverse regression and the decomposition model. Lastly, we calculated the amount of wage discrimination according to disability. Findings: The wage disparity due to market characteristics shows a 163.39% total wage disparity, which indicates that there is serious wage discrimination. Finally, the amount of wage discrimination according to disability is 427,020 KRW (372.42 USD) per month. Despite the incentives provided to firms to employ persons with disabilities in Korea, those with disabilities still receive lower wages than those without disabilities. Research limitations/implications: We provide the basis for calculating the appropriate contributions and incentives for the current in-force employment inducement system for individuals with disabilities. Originality/value: This study provides important implications for employment and wage policies for people with disabilities by identifying which factors among human resource characteristics and market characteristics cause the total wage gap between the disabled and non-disabled people and whether the cause is resource effect or wage discrimination.
Keywords: 650; Wage Disparity; Wage Discrimination; Employees With Disabilities; Employees Without Disabilities